PERAN KEMENTERIAN AGAMA (KUA) DALAM MENCEGAH PERNIKAHAN DINI DI BUNTOK KALIMANTAN TENGAH - Aulia Ulfa; Achmad Gazali (ADISAM PUBLISHER, 2025)
This study examines the role of the South Hamlet KUA (Office of Religious Affairs) in preventing early marriage and the factors that support and hinder the role of the South Hamlet KUA in preventing early marriage in Buntok, Central Kalimantan. Early marriage is a marriage between a man and a woman who are still under the age of 19. Early marriage remains a complex issue, influenced by various factors such as economics, culture, education, pregnancy outside of marriage, and religious understanding. This study uses a qualitative approach with field research and is supported by references related to the theme discussed in this study. The object of this study is the role of the South Hamlet KUA in preventing early marriage in Buntok, Central Kalimantan. The subject of this study is one extension worker at the South Hamlet KUA. To obtain field data, interviews were used as the main data source, along with documentation. The results of the study conclude that the South Hamlet KUA acts as a motivator and guide. The South Hamlet KUA collaborates with various other institutions such as the Religious Court, the Buntok Health Centre and the Baru Health Centre, as well as the Population and Civil Registry Office. There are two South Hamlet KUA programmes to prevent early marriage: socialisation and marriage guidance before the marriage takes place. A supporting factor for the South Hamlet KUA in preventing early marriage is the availability of operational funds. The obstacle faced by the South Hamlet KUA in preventing early marriage is the lack of awareness and understanding among the community. The solution to the obstacles faced by the South Hamlet KUA in preventing early marriage is to consistently implement government programmes